Natural aluminosilicate nanotubes loaded with RuCo as nanoreactors for Fischer-Tropsch synthesis. Issue 1 (31st December 2022) - Mazurova, Kristina; Glotov, Aleksandr; Kotelev, Mikhail; Eliseev, Oleg; Gushchin, Pavel; Rubtsova, Maria; Vutolkina, Anna; Kazantsev, Ruslan; Vinokurov, Vladimir; Stavitskaya, Anna
ABSTRACT: Following nanoarchitectural approach, mesoporous halloysite nanotubes with internal surface composed of alumina were loaded with 5–6 nm RuCo nanoparticles by sequential loading/reduction procedure. Ruthenium nanoclusters were loaded inside clay tube by microwave-assisted method followed by cobalt ions electrostatic attraction to ruthenium during wetness impregnation step. Developed nanoreactors with bimetallic RuCo nanoparticles were investigated as catalysts for the Fischer-Tropsch process. The catalyst with 14.3 wt.% of Co and 0.15 wt.% of Ru showed high activity (СO conversion reached 24.6%), low selectivity to methane (11.9%), CO2 (0.3%), selectivity to C5+ hydrocarbons of 79.1% and chain growth index (α) = 0.853. Proposed nanoreactors showed better selectivity to target products combined with high activity in comparison to the similar bimetallic systems supported on synthetic porous materials. It was shown that reducing agent (NaBH4 or H2 ) used to obtain Ru nanoclusters at first synthesis step played a very important role in the reducibility and selectivity of resulting RuCo catalysts. GRAPHICAL ABSTRACT: uf0001